Chemical diversity and anti-proliferative activity of marine algae. Issue 14 (18th July 2019) - Palanisamy, Satheesh Kumar; Arumugam, Velusamy; Rajendran, Samyutha; Ramadoss, Anandhan; Nachimuthu, Subash; Peter D., Magesh; Sundaresan, Umamaheswari
Abstract: The chemical diversity of three macroalgae ( Ulva reticulata, Sargassum wightii, Gracilaria sp) were determined using the GC-MS method with principal component analysis (PCA) and their potential efficacy against human pathogens and cervical carcinoma cells evaluated using MTT bioassay method. Our results showed that >30 metabolites were detected in three seaweeds, among these, steroids and fatty acids are the most dominant chemical group that highly contributes to discriminate this species. The PCA of GC-MS mass spectral variables showed a clear discrimination between three different species based on the phytochemical diversity of seaweeds. The extracts of U. reticulata exhibited anti-microbial activity with Pseudomonas aeruginosa (6.00 mm) and showed potential anti-proliferative activity against the HeLa cells (IC50 37 µmol/L) at concentration 1–50 µM treatment. Results of this study concluded that PCA analysis of mass spectral variables could be utilized as a reliable tool for species discrimination and chemotaxonomic classification of seaweeds. Abstract :